P lasmodium falciparum gametocyte burden in a Tanzanian heterogeneous transmission setting - Charles Mulamba; Olukayode G. Odufuwa; Prisca A. Kweyamba; Linda O. Lazaro; Muhamed S. Chabo; Janeth J. Kamage; Katharina Kreppel; Ally I. Olotu; Chris L. Williams (Malaria Journal)
Abstract Background Malaria transmission depends on the presence of gametocytes in the peripheral blood of infected human hosts. Understanding malaria infectious reservoirs enables transmission-blocking interventions to target the most important hosts for the disease. This study characterized the distribution of gametocyte carriage as a baseline for the clinical evaluation of a Pfs25-based transmission-blocking vaccine candidate in Bagamoyo, Tanzania. Methods A malaria survey was conducted in five locations from May to August 2022. A total of 467 participants—192 children (5–12 years), 65 adolescents (13–17 years) and 210 adults (18–45 years)—were enrolled. Malaria was detected using three methods: rapid diagnostic tests, light microscopy and quantitative polymerase chain reaction. The geometric mean of the gametocyte density, and weighted arithmetic mean of the gametocytes sex ratio were estimated. Results Overall, 23.5% (110/467) of the participants tested positive for malaria parasites, with the majority of positives (> 92%) being Plasmodium falciparum. The overall gametocytaemia was 5.6%, with a percent positivity of 6.8% (13/192), 6.2% (4/65) and 4.3% (9/210), in children, adolescents, and adults, respectively. The geometric mean gametocyte density (gametocytes/μL) was greater in adults (124.6) than in children (71.7) and adolescents (50.5). Regression analysis revealed that gametocytes were more likely to be present among male participants than among female participants [ORa: 2.79 (95% CI: 1.19 – 6.59) p = 0.019]. The gametocyte sex ratio in children and adult gametocyte carriers was similar but greater than that in adolescents. Conclusion The observed gametocyte densities and distribution across age groups suggest the need for malaria transmission-blocking interventions to target all populations in heterogeneous transmission settings. The implication of targeting only children may leave residual malaria transmission and reinfection from the left-out groups. Graphical abstract